Academic Flow Among High-achieving Students of Senior High Schools: The Role of Self-regulated Learning and Task Commitment - Wahyu Indah Safitri; Abdul Muhid; Moh Sholeh; Jainudin Jainudin (Indonesian Psychological Research, 2025)
This study aims to examine the effect of self-regulated learning, self-esteem, social support, and task commitment on academic flow among high-achieving students at State Senior High Schools in Sidoarjo, Indonesia. This study used a correlational quantitative design. Data were collected using the self-regulated learning scale, the self-esteem scale, the social support scale, the task commitment scale, and the academic flow scale. Participants of this study involved 80 students from a total population of 3,204 students who were selected using the quota sampling technique. The result of Partial Least Square Structural Equation Modeling (PLS-SEM) indicated SRMR = 0.073, and NFI = 0.81, R2=0.484. This result means that self-regulated learning, self-esteem, social support, and task commitment simultaneously explain 48.4% of the variance in academic flow. Further analysis showed that of the four variables, only self-regulated learning and task commitment have a significant effect, implying that higher self-regulated learning and more commitment to the tasks lead to more intense academic flow. This finding differs from some previous study and implied that the students need to be facilitated with self-regulated learning-oriented learning design and need for improvement in task commitment to intensify academic flow that eventually will maintain and exert their optimal performance.